The Sand Fly Salivary Protein Lufaxin Inhibits the Early Steps of the Alternative Pathway of Complement by Direct Binding to the Proconvertase C3b-B - Mendes-Sousa, Antonio F.; Vale, Vladimir Fazito do; Silva, Naylene C. S.; Guimaraes-Costa, Anderson B.; Pereira, Marcos H.; Sant’Anna, Mauricio R. V.; Oliveira, Fabiano; Kamhawi, Shaden; Ribeiro, José M. C.; Andersen, John F.; Valenzuela, Jesus G.; Araujo, Ricardo N. (Frontiers in Immunology, 2017)
Saliva of the blood feeding sand fly Lutzomyia longipalpis was previously shown to inhibit the alternative pathway (AP) of the complement system. Here, we have identified Lufaxin, a protein component in saliva, as the inhibitor of the AP. Lufaxin inhibited the deposition of C3b, Bb, Properdin, C5b, and C9b on agarose-coated plates in a dose-dependent manner. It also inhibited the activation of factor B in normal serum, but had no effect on the components of the membrane attack complex. Surface plasmon resonance (SPR) experiments demonstrated that Lufaxin stabilizes the C3b-B proconvertase complex when passed over a C3b surface in combination with factor B. Lufaxin was also shown to inhibit the activation of factor B by factor D in a reconstituted C3b-B, but did not inhibit the activation of C3 by reconstituted C3b-Bb. Proconvertase stabilization does not require the presence of divalent cations, but addition of Ni2+ increases the stability of complexes formed on SPR surfaces. Stabilization of the C3b-B complex to prevent C3 convertase formation (C3b-Bb formation) is a novel mechanism that differs from previously described strategies used by other organisms to inhibit the AP of the host complement system.